2001
DOI: 10.1111/j.1574-6968.2001.tb09440.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of clinicalSerratia marcescensisolates: a comparison of PCR-based methods

Abstract: The polymerase chain reaction (PCR)-based procedures of randomly amplified polymorphic DNA (RAPD) and repetitive element (RE)-based PCR were used to amplify total DNA prepared from each of 62 clinical Serratia marcescens isolates. Three different random primers, designated 1060, 1254 and 1283, were used individually in RAPD-PCR. Primers representing enterobacterial repetitive intergenic consensus (ERIC) sequences, extragenic palindromic (REP) elements, and polymorphic GC-rich repetitive sequences (PGRS) consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This genomic fingerprinting technique was chosen for several reasons; i) it generates specific strain patterns obtained by the amplification of repetitive DNA elements present along the E. coli genome [21], ii) the technique has proved more discriminatory than 16S rRNA PCR methods and restriction fragment length polymorphism [22, 23], and provides discriminatory power similar to randomly amplified polymorphic DNA (RAPD) [24]. In addition, the REP protocol is simpler and allows handling of a larger number of samples than other genomic DNA protocols, such as pulsed field gel electrophoresis, for molecular typing [22].…”
Section: Discussionmentioning
confidence: 99%
“…This genomic fingerprinting technique was chosen for several reasons; i) it generates specific strain patterns obtained by the amplification of repetitive DNA elements present along the E. coli genome [21], ii) the technique has proved more discriminatory than 16S rRNA PCR methods and restriction fragment length polymorphism [22, 23], and provides discriminatory power similar to randomly amplified polymorphic DNA (RAPD) [24]. In addition, the REP protocol is simpler and allows handling of a larger number of samples than other genomic DNA protocols, such as pulsed field gel electrophoresis, for molecular typing [22].…”
Section: Discussionmentioning
confidence: 99%
“…BOX elements have since been identified in P. aeruginosa as well as Enterococcus faecalis (Malathum et al, 1998;McSpadden Gardener et al, 2000). ERIC-PCR has been successfully applied to P. aeruginosa as well as Listeria monocytogenes, Serratia marcescens, Escherichia coli, Staphylococcus aureus, Enterococcus faecalis, Staphylococcus epidermidis and Acinetobacter baumannii (Jersek et al, 1999;Kang & Dunne, 2003;Lau et al, 1995;Patton et al, 2001). This study demonstrated that ERIC-PCR and BOX-PCR were equally effective in characterizing clinical isolates of P. aeruginosa.…”
Section: Applications Of Rep-pcr Assaysmentioning
confidence: 99%
“…The extracted DNA from each positive isolate above was used as a template for PCR with Polymorphic GC-rich Repetitive Sequences (PGRS) primers (Table 1) to discriminate Mycobacterium isolates to remove the same isolates and get representative Mycobacterium stains for further following assay. The PCR amplification was performed as described previously [21]. After PCR amplification, 5 µl of the PCR reaction mixture was separated on a 6% polyacrylamide gel (acrylamide: N-N′-methylene bisacrylamide 29:1) using a Bio-Rad system.…”
mentioning
confidence: 99%